Does sustainability disclosure improve analysts’ forecast accuracy? Evidence from European banks - Albert Acheampong; Tamer Elshandidy (Financial Innovation)
Abstract In this study, we investigate the extent to which sustainability disclosures in the narrative sections of European banks’ annual reports improve analysts’ forecasting accuracy. We capture sustainability disclosures with a machine learning approach and use forecast errors as a proxy for analysts’ forecast accuracy. Our results suggest that sustainability disclosures significantly improve analysts’ forecasting accuracy by reducing forecast errors. In a further analysis, we also find that the introduction of Directive 2014/95/European Union is associated with increased disclosure content, which reduces forecast error. Collectively, our results suggest that sustainability disclosures improve forecast accuracy, and the introduction of the new EU directive strengthens this improvement. These results hold after several robustness tests. Our findings have important implications for market participants and policymakers.